Bewußtseinslust. Das freie Spiel der Vermögen in Kants Kritik der Urteilskraft als transzendentales Verhältnis - Weiß, Michael Bastian (Studia Kantiana, 2023)
Kant´s critical philosophy as a whole operates on the condition of possibility that the faculties of pure reason can be isolated analytically in order to evaluate them, while at the same time they work together in various effective forms of inter-play. As one of these forms, Kant in the Critique of the Power of Judgment introduces the "free play of imagination and understanding", which plays an important role in setting together the four moments of the aesthetic judgement. Within the last two decades or so it has been discussed widely how this cooperation between these two faculties works, but it barely has been reflected on the question how to address the "free play" properly in terms of a methodological classification. This paper follows the various contexts in which the "free play" is referred to, focusses primarily on the dysfunctional cases in which the cooperation between the two faculties fails or comes to a halt and thus evaluates the basic structure of the "free play" under the perspective of theoretical technique on the horizon of transcendental philosophy. The aim is to eventually propose a more precise title of the free play or alternatively give a reason why such a labelling could not be possible after all.